2002
DOI: 10.1038/417463a
|View full text |Cite
|
Sign up to set email alerts
|

The catalytic pathway of horseradish peroxidase at high resolution

Abstract: A molecular description of oxygen and peroxide activation in biological systems is difficult, because electrons liberated during X-ray data collection reduce the active centres of redox enzymes catalysing these reactions. Here we describe an effective strategy to obtain crystal structures for high-valency redox intermediates and present a three-dimensional movie of the X-ray-driven catalytic reduction of a bound dioxygen species in horseradish peroxidase (HRP). We also describe separate experiments in which hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
787
2
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 853 publications
(852 citation statements)
references
References 27 publications
47
787
2
3
Order By: Relevance
“…For ferryl the distance from the iron atom to the center of the ligand electron density is 1.9 Å, which is shorter than the normal Fe‐O distance of 2.2–2.3 Å in most aquo‐metHb and metMb structures. The modeled Fe‐O distance of 1.9 Å is consistent with previously reported ferryl complexes in peroxidases 39. The occupancy of water coordinated to the iron atom of metHb may make it less stable.…”
Section: Discussionsupporting
confidence: 88%
“…For ferryl the distance from the iron atom to the center of the ligand electron density is 1.9 Å, which is shorter than the normal Fe‐O distance of 2.2–2.3 Å in most aquo‐metHb and metMb structures. The modeled Fe‐O distance of 1.9 Å is consistent with previously reported ferryl complexes in peroxidases 39. The occupancy of water coordinated to the iron atom of metHb may make it less stable.…”
Section: Discussionsupporting
confidence: 88%
“…The root mean square displacements of the C␣ atoms between the ligand-free and the oxy forms are small and equal to 0.182, 0.190, and 0.163 Å for the three HmuO molecules in the asymmetric unit. In agreement with the resonance Raman results, O 2 binds end-on to the heme iron with a bend angle of ϳ110 o , which is more acute than the bend angle reported for the high resolution crystal structures of oxy forms of Mb (122 o (47). In HmuO, the distance between the terminal oxygen atom of bound O 2 and the porphyrin ␣-meso-carbon atom is ϳ3.4 Å.…”
Section: Resultssupporting
confidence: 70%
“…The discrepancy between spectroscopic and crystallographic data prompted us to reexamine the Ni coordination and is explained by the effect of radiation on the oxidation state of Ni. It has been observed that radiation-induced changes of the metal center's oxidation state can take place during exposure to x-rays (26). The reduction of Ni(III) in the resting enzyme during x-ray data collection became evident from a difference Fourier omit map calculated with an initial fraction of data collected in a multiple-wavelength anomalous dispersion experiment (lowdose data set, see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%